The impact of diet and oral hygiene on dental caries among Turkish children: A cross-sectional study - Ozge Yesildemir; Melisa Ozay Sekendiz; Duygu Ağagündüz; Ferenc Budán (PLoS ONE, 2025)
Background Dental caries remains one of the most prevalent chronic conditions affecting children worldwide, yet they are largely preventable through modifiable factors such as diet and oral hygiene. This study aimed to examine the associations between dietary intake, oral hygiene practices, anthropometric measurements, and dental caries in children. Methods This cross-sectional study was conducted in Bursa, Türkiye, between 1 October 2023 and 20 February 2024 with 210 children aged 5–12 years. Data was collected through a structured questionnaire on sociodemographic factors, oral hygiene, and a food frequency questionnaire related to dental health. Body weight and height were measured, and dental examinations were performed by a trained dentist using DMFT/dmft indices. Results Mean DMFT and dmft scores were 0.9 ± 1.3 and 3.9 ± 2.8, respectively. Children who brushed their teeth had significantly lower caries scores ( p < 0.001); brushing twice daily was associated with lower dmft scores ( p < 0.001). Caries scores did not differ significantly by body mass index ( p > 0.05). Higher DMFT scores were associated with citrus fruits ( β = 0.322, p < 0.001), white bread ( β = 0.423, p < 0.001), and fruit juice ( β = 0.050, p < 0.05) consumption. Higher dmft scores were linked to chocolate ( β = 0.286), biscuits, cookies, and cakes ( β = 0.448), chips ( β = 0.179), and carbonated soft drinks ( β = 0.789) ( p < 0.001). Conclusions These results highlight the importance of promoting healthy eating and proper oral hygiene to prevent childhood dental caries and suggest that early oral health status may have broader implications for long-term systemic health, warranting further longitudinal investigation.